Route for Conversion of Furfural to Ethylcyclopentane - Bredihhin, Aleksei (ACS Omega, 2018)
[Image: see text] A method for conversion of furfural, widely available platform chemical from biomass, to ethylcyclopentane, is reported. Ethylcyclopentane is a cyclic alkane with a relatively high octane number (RON 67, bp 103 °C) and could potentially serve as a drop-in biofuel. The synthetic route includes a transformation of furfural to 1-(furan-2-yl)propan-1-ol that is further subjected to Piancatelli rearrangement to give 5-ethyl-4-hydroxycyclopent-2-en-1-one. The subsequent hydrodeoxygenation affords ethylcyclopentane in 48% isolated yield.